Impact of BRCA mutations, age, surgical indication, and hormone status on the molecular phenotype of the human Fallopian tube - Ian Beddows; Svetlana Djirackor; Dalia K. Omran; Euihye Jung; Natalie NC Shih; Ritu Roy; Aaron Hechmer; Adam Olshen; Guillaume Adelmant; Ann Tom; Jacob Morrison; Marie Adams; et al. (Nature Communications)
Abstract The human Fallopian tube (FT) is an important organ in the female reproductive system and has been implicated as a site of origin for pelvic serous cancers, including high-grade serous tubo-ovarian carcinoma (HGSC). We have generated comprehensive whole-genome bisulfite sequencing, RNA-seq, and proteomic data of over 100 human FTs, with detailed clinical covariate annotations. Our results challenge existing paradigms that extensive epigenetic, transcriptomic and proteomic alterations exist in the FTs from women carrying heterozygous germline BRCA1/2 pathogenic variants. We find minimal differences between BRCA1/2 carriers and non-carriers prior to loss of heterozygosity. Covariates such as age and surgical indication can confound BRCA1/2-related differences reported in the literature, mainly through their impact on cell composition. We systematically document and highlight the degree of variations across normal human FT, defining five groups capturing major cellular and molecular changes across various reproductive stages, pregnancy, and aging. We are able to associate gene, protein, and epigenetic changes with these and other clinical covariates, but not heterozygous BRCA1/2 mutation status. This sheds new light into prevention and early detection of tumorigenesis in populations at high-risk for ovarian cancer.